Transfer effects on sound localization performances from playing a virtual three-dimensional auditory game - Honda, Akio; Shibata, Hiroshi; Gyoba, Jiro; Saitou, Kouji; Iwaya, Yukio; Suzuki, Yôiti (Applied acoustics, 2007)
Transfer effects of playing an auditory game with a virtual auditory display (VAD) were investigated. Furthermore, we analyzed the effects of playing the VAD game on sound localization performance under subjects’ own head-related transfer functions (HRTFs) and HRTFs fitted from those of 16 other adults. Participants performed sound localization tasks initially and 2 weeks later to show the effects. The VAD game players were of three groups, using own HRTFs, fitted HRTFs, and no playing (control). The VAD game-playing results revealed that: (1) the hit rate of the sound localization task for real sound sources increased approximately 20%; (2) the vertical and horizontal localization error decreased significantly; (3) sound localization performance using fitted HRTFs was similar to performance using own HRTFs. Follow-up tests revealed that transfer effects persisted more than 1 month, suggesting that the effects of playing the VAD game transfer to sound localization performance.